2005
DOI: 10.1007/s00125-005-0001-x
|View full text |Cite
|
Sign up to set email alerts
|

Visual fields correlate better than visual acuity to severity of diabetic retinopathy

Abstract: Aims/hypothesis: We compared the outcomes of perimetric and visual acuity tests in patients with diabetic retinopathy. Methods: We examined 59 diabetic patients with different degrees of retinopathy using stereo fundus photography in accordance with the Early Treatment of Diabetic Retinopathy Study (ETDRS) and fluorescein angiography. Conventional white-on-white perimetry (WWP) and short wavelength automated perimetry (SWAP) were performed and analysed with reference to normal values. Visual acuity was measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
54
0
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 27 publications
6
54
0
3
Order By: Relevance
“…However, Hudson and colleagues did not include eyes without oedema in their analyses and also did not characterise the perifoveolar capillary network. Although it cannot be excluded that the difference in results could depend on our use of a different classification of macular oedema, our multivariate analysis showed that FAZ and PIAs together was the only explanatory variable not only for SWAP but also for WWP defects, as previously described in more detail [9]. Similar observations on SWAP have been published by Remky et al [12].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…However, Hudson and colleagues did not include eyes without oedema in their analyses and also did not characterise the perifoveolar capillary network. Although it cannot be excluded that the difference in results could depend on our use of a different classification of macular oedema, our multivariate analysis showed that FAZ and PIAs together was the only explanatory variable not only for SWAP but also for WWP defects, as previously described in more detail [9]. Similar observations on SWAP have been published by Remky et al [12].…”
Section: Discussionsupporting
confidence: 85%
“…Fields were evaluated in terms of the pattern deviation probability maps included in the Statpac interpretation tool [8]. Since no Statpac interpretation was available for SWAP 10-2, a normal database including 180 eyes of 90 healthy subjects was constructed for the generation of a Statpac program including pattern deviation probability maps [9]. In these maps, test point locations with significantly reduced differential light sensitivity are flagged as abnormal after elimination of effects of media opacities, such as cataract.…”
Section: Visual Field Testsmentioning
confidence: 99%
“…In fact, loss of oscillatory potentials on electroretinograms predicts the onset of proliferative retinopathy better than vascular lesions seen on fundus photographs or capillary nonperfusion visualized by fluorescein angiograms (40). Electroretinograms and psychophysical tests are primarily used in research settings, but recent reports using clinically available visual field test modifications (short-wave automated perimetry and frequency doubling perimetry) reveal field defects in patients with little or no vascular retinopathy (41,42), and visual fields predict the severity of retinopathy better than visual acuity (43). Together, these findings strongly suggest that functional tests are more sensitive indicators of retinal integrity than fundus photographs or optical coherence tomography and may serve as useful end points for clinical trials, but they must be validated first.…”
Section: Diabetic Retinopathy: Beyond Glucose-induced Microvascular Dmentioning
confidence: 99%
“…[71][72][73] Most recently, tests of visual fields have also been reported to be more indicative of functional deficiency than visual acuity tests when determining retinopathy severity. 74 Frequency doubling technology (FDT) perimetry is now being used to investigate the neuronal consequences of early diabetic retinopathy by testing the visual field. Studies applying the technology have revealed severe impairment of retinal function, particularly affecting the inner retina and rod photoreceptors, even before visual acuity decline.…”
Section: Research For Improved Therapies Novel Endpointsmentioning
confidence: 99%